The eternal return of the sustainable. Discursive construction of a modern city in Córdoba (Argentina) - Quevedo, Cecilia Mercedes (2016)
From a semiotic analysis of the press notes in supplement Pensar Córdoba of La Voz del Interior newspaper, published in the city of Cordoba (Argentina), this article, from a materialistic reading, focuses on two aims. At first, exploring the discursive arrangement, which, based on the concept of sustainability, is established as suturing strategy of social conflict at the city. Second, an analysis from ideological critique of what the supplement projected as classist topologies, that is, meanings based on a hegemonic cartography of some traditional −and now privileged by the housing market− neighborhoods.